The utility of serum amyloid A and other acute-phase reactants determination in ambulatory care COVID-19 patients: Serum amyloid A in ambulatory care COVID-19 patients - Jegorovic, Boris; Nikolic, Aleksandra; Milinkovic, Neda; Ignjatovic, Svetlana; Sipetic Grujicic, Sandra (Journal of Medical Biochemistry, 2023)
Background: The unpredictable course of Coronavirus Disease 19 (COVID-19) is making good severity assessment tools crucial. This study aimed to assess the usefulness of serum amyloid A (SAA) and other acute-phase reactants (APRs) in ambulatory COVID-19 patients and identified relationships between these markers and disease outcomes. Methods: From August to November 2020, patients seen in the outpatient department of the Clinic for Infectious and Tropical Diseases (Belgrade, Serbia) with confirmed COVID-19 were included. Based on World Health Organization criteria, patients were classified into mild, moderate, and severe disease groups. SAA, C-reactive protein (CRP), interleukin-6 (IL-6), procalcitonin (PCT), ferritin, fibrinogen, D-dimer, albumin, and transferrin were measured. The Receiver operator characteristic (ROC) curve analysis was used for the classification characteristics assessment of individual APRs for the severity of illness, hospitalization, and survival. The median values of all APRs were compared between COVID-19 severity groups, hospitalized and non-hospitalized patients, and survivors and non-survivors. Results: Higher levels of SAA, CRP, IL-6, PCT, and lower levels of transferrin and albumin were observed in severe cases, hospitalized patients, and non-survivors. Based on ROC curve analysis AUC for SAA has fair classification performance for disease severity (0.794) and death (0.732) and good performance for hospitalization (0.853). Conclusion: SAA is a valuable marker in everyday practice for assessing COVID-19 severity and prognosis in ambulatory patients.